Fractographic Regularities in Fatigue Failure of 17Mn1Si Steel; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Maruschak P.; Panin S. V. Sergey Viktorovich; Vlasov I.; Danyliuk I.; Bishchak R. (Advanced Materials and Nanotechnology, 2014)
Title screen